Functional MRI-specific alterations in frontoparietal network in mild cognitive impairment: an ALE meta-analysis - Yang, Xinyi; Wu, Huimin; Song, Yu; Chen, Shanshan; Ge, Honglin; Yan, Zheng; Yuan, Qianqian; Liang, Xuhong; Lin, Xingjian; Chen, Jiu (Frontiers in Aging Neuroscience, 2023)
Background: Mild cognitive impairment (MCI) is a transitory phase between healthy elderly and Alzheimer's disease (AD) with worsening cognitive impairment. Some functional MRI (fMRI) research indicated that the frontoparietal network (FPN) could be an essential part of the pathophysiological mechanism of MCI. However, damaged FPN regions were not consistently reported, especially their interactions with other brain networks. We assessed the fMRI-specific anomalies of FPN in MCI by analyzing brain regions with functional alternations. Methods: PubMed, Embase, and Web of Science were searched to screen neuroimaging studies exploring brain function alternations in FPN in MCI using fMRI-related indexes, including the amplitude of low-frequency fluctuation, regional homogeneity and functional connectivity. We integrated distinctive coordinates by activating likelihood estimation, visualizing abnormal functional regions, and concluding functional alterations of FPN. Results: We selected 29 studies and found specific changes in some brain regions of FPN. These included the bilateral dorsolateral prefrontal cortex, insula, precuneus cortex, anterior cingulate cortex, inferior parietal lobule, middle temporal gyrus, superior frontal gyrus and parahippocampal gyrus. Any abnormal alternations in these regions depicted interactions between FPN and other networks. Conclusion: The study demonstrates specific fMRI neuroimaging alterations in brain regions of FPN in MCI patients. This could provide a new perspective on identifying early-stage patients with targeted treatment programs.